Legal Politics of Financial Relations between the Central and Regional Governments: Natural Resource Utilization - Furqon, Eki; Shodiq, Edi Mulyadi Zafar (Unifikasi : Jurnal Ilmu Hukum, 2024)
Population growth and welfare development in each province, particularly Banten, have been inadequately supported by the management of natural resources. In fact, such conditions are prevalent across Indonesia. Accordingly, the study aims to investigate the regulation of central and regional relations under Law Number 1 of 2022: Financial Relations between the Central and Regional Governments, as well as their Ideal Format based on Natural Resource Utilisation in Banten province. The study employed normative juridical methods. The study took place in Banten Province. The findings are that the financial administration system, regulating central and regional relations, is law number 1 of 2022; financial relations between central and regional governments, which provide regional income sources, manage transfers to regions, manage regional expenditure, give authority to carry out financing regions, and implement national fiscal policy synergies in a fair, transparent, accountable, and harmonious manner. Framework of the Unitary State of the Republic of Indonesia: optimal structure of central and regional relations—the utilisation of natural resources in Banten Province. In particular, the management of natural and other resources, as stated in the Profit Sharing Fund layout, which is standardised in the law on central and regional financial relations, is referred to as implementing regional autonomy through a clustering mechanism between regions while considering the ecological and conditional factors (economic, social, and political conditions). To summarise, harmonisation and coordination between the central and Banten provincial governments are highly required. In addition, the Banten provincial government should immediately issue derivative regulations to facilitate policy implementation.